Analisis Penerapan Disiplin Kerja Anggota Tim Penggerak PKK Kabupaten Bungo - Purnamawati, Purnamawati; Nasir, Muhammad; Anggraini, Zepa; Susanto, Joko (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2020)
This research departs from the background of the problem of the low work discipline of the members of the PKK Motivating Team in Bungo Regency so that they have not been able to achieve good performance. The purpose of this study was to determine the application, barriers, and efforts to overcome obstacles in the application of work discipline members of the Bungo District PKK Driving Team. This research uses descriptive research with a qualitative approach. The population in this study were the chairman and all members of the PKK Movement Team for Bungo Regency, with a total sample of fifteen people. The results showed that the application of work discipline in the Office of the PKK Movement Team in Bungo Regency has not been going well, it can be seen from the dimensions of timeliness and dimensions of work responsibility that have not been implemented properly. The inhibiting factor is the absence of sanctions for members who are not disciplined at work, and there are still members who are not responsible for completing the workload given. Efforts are being made, namely by applying sanctions in the form of fines, conducting member coaching once a month.